(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate microbiological characteristics of patients with skin and soft tissue infections treated with antibiotics at Thong Nhat Hospital. Method: A cross-sectional descriptive study was conducted on the medical reports of patients diagnosed with skin and soft tissue infections at Thong Nhat Hospital from January 2024 to December 2024. Survey parameters included baseline characteristics of patients, culture characteristics, and microbiological results. Results: A total of 463 medical reports were included in the analysis of the study. The median age was 65 (47-75), 53.78% were male patients. There were 349 patients (75.38%) who had their specimens cultured, of which 67.62% were cultured before using antibiotics. Among the isolated bacterial strains, Staphylococcus aureus had the highest rate (28.87%), of which 80.36% were Methicillin-resistant Staphylococcus aureus (MRSA). The sensitivity rate of MRSA to Vancomycin, Teicoplanin, Linezolid, Tigecycline reached 99-100%. The Gram-negative bacteria isolated were mainly Escherichia coli (17.53%), Klebsiella pneumoniae (8.51%), Pseudomonas aeruginosa (6.45%). The resistance mechanisms recorded in Gram-negative bacteria were carbapenemase secretion (13.72%), AmpC (3.72%) and reduced outer membrane permeability (8.82%). Conclusion: The situation of microbiological specimen culture in patients with skin and soft tissue infections was relatively good at Thong Nhat Hospital. Continued monitoring of antibiotic resistance is needed to help improve the effectiveness of infection treatment.